تنمية المهارات الادراكية المعرفية لدى الطفل التوحدي باعتماد برنامج تيتش - مسعود بوجمل; ياسمين جعيد; بن يطو جلول (My University, 2023)
This study is conducted for testing the cognitive developing skills of an autistic child, using TEACCH program among the sample of six (6) children suffering from Autism Spectrum Disorder, aged from six to twelve years, adopting one-group design (pre and post measurement). The quasiexperimental method is adopted, by using research means in observation, interview and testing cognitive skills. And to achieve the aims of the study, special cognitive developing skills exercises and activities were used which were taken from TEACCH program as well as the application form. The statistical processing data with the SPSS, where arithmetic average and standard deviation were calculated as well as doing Wilcoxon test, demonstrated the program efficiency of cognitive developing skill of autistic child with the obtained post-measurement results in which there were improvement. Keywords: cognition, TEACCH, autism.